2021
DOI: 10.1037/edu0000662
|View full text |Cite
|
Sign up to set email alerts
|

Engaging caregivers and children in picture books: A family-implemented mathematical language intervention.

Abstract: The goal of this study was to evaluate immediate and delayed effects of a caregiver-implemented picture book intervention to support children's mathematical language and numeracy skills. Eightyfour 3-to 5-year-olds (M age = 4.14) were randomly assigned to intervention (n = 40) or active control (n = 44) conditions. Participants in the intervention condition received three researcher-designed picture books with embedded mathematical language content. The active control group received similar books without mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 56 publications
0
68
0
Order By: Relevance
“…A similar study randomly assigned typically developing preschool‐aged U.S. English‐speaking children (most of whom were White) and their family caregivers (nearly all of whom were college‐educated mothers) to read and discuss either three math (intervention) or nonmath (control) storybooks (Purpura et al, 2021). Participants in the intervention condition received three researcher‐developed books featuring 17 core (e.g., more, different, few ) and story‐specific (e.g., just enough ) math terms.…”
Section: Language and Math Instructionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study randomly assigned typically developing preschool‐aged U.S. English‐speaking children (most of whom were White) and their family caregivers (nearly all of whom were college‐educated mothers) to read and discuss either three math (intervention) or nonmath (control) storybooks (Purpura et al, 2021). Participants in the intervention condition received three researcher‐developed books featuring 17 core (e.g., more, different, few ) and story‐specific (e.g., just enough ) math terms.…”
Section: Language and Math Instructionmentioning
confidence: 99%
“…As the developmental links between language and math have become clearer, a growing body of math language interventions has been developed and rigorously tested. In this literature, compelling evidence suggests that certain forms of language instruction can strengthen young children’s number knowledge (Gibson et al, 2020; Purpura et al, 2021) and performance in word‐problem solving (Fuchs et al, 2021). But currently, there is no evidence that standalone or embedded language instruction can improve children’s arithmetic performance (Hassinger‐Das et al, 2015; Jordan et al, 2012; Powell & Driver, 2015).…”
Section: Summary Implications and Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When considering early childhood instruction, this finding suggests that opportunities to support preschoolers in developing their mathematical language skills may provide benefits. For example, brief storybook interventions have been found to improve children's mathematical language (Purpura et al, 2021). Indeed, recent experimental studies have shown that reading interventions focusing on spatial and numerical words (e.g., more, less, near, far) can lead to improvements in both children's mathematical language and mathematics achievement (Purpura et al, 2021;Hassinger-Das et al, 2015;Purpura et al, 2016).…”
Section: Mathematical Language As a Full Mediatormentioning
confidence: 99%
“…For example, brief storybook interventions have been found to improve children's mathematical language (Purpura et al, 2021). Indeed, recent experimental studies have shown that reading interventions focusing on spatial and numerical words (e.g., more, less, near, far) can lead to improvements in both children's mathematical language and mathematics achievement (Purpura et al, 2021;Hassinger-Das et al, 2015;Purpura et al, 2016). This contrasts with the mixed findings of studies to promote children's mathematics achievement by improving their ANS (Honoré & Noël, 2016;Park et al, 2016;Wang et al, 2020).…”
Section: Mathematical Language As a Full Mediatormentioning
confidence: 99%